PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS - Fitriana, Ita Dwi; Wijayanti, Anita; Dewi, Riana Rachmawati (Universitas Nusantara PGRI Kediri, 2020)
This study aims to determine the effect of cash turnover, accounts receivable turnover, and inventory turnover on the profitability. This research uses secondary data in conducting analysis. The dependent variables are profitability and independent variables, cash turnover, receivable turnover and inventory turnover. The population of this research is companies listed on the IDX in 2013-2019.The sample used in this study is 35 samples. Testing the hypothesis of this study using multiple linear regression test. The results showed that: 1) cash turnover does not have a significant effect on profitability, 2)receivable turnover does not have a significant effect on profitabilit, 3)inventory turnover has a significant effect on profitability.